2018
DOI: 10.1177/1093526618755200
|View full text |Cite
|
Sign up to set email alerts
|

FTL c.-168G>C Mutation in Hereditary Hyperferritinemia Cataract Syndrome: A New Italian Family

Abstract: We describe a new Italian family with 7 members affected by hereditary hyperferritinemia cataract syndrome (HHCS), an uncommon autosomal dominant disease caused by mutations of the iron-responsive element (IRE) of the ferritin light chain (FTL) gene determining its overexpression. The family diagnosis of HHCS took place after finding high ferritin levels in a 6-year-old girl. Seven members of the family had bilateral and symmetrical cataracts, normal iron, and hematological parameters except for high serum fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Infants in neonatal intensive care unit (NICU) have greater chances of developing sensorineural hearing loss (SNHL) because of the presence of multiple risk factors [ 12 ]. It has been reported that hereditary hyperferritinemia cataract syndrome (HHCS) should be considered in the differential diagnosis of childhood hyperferritinemia, especially in the presence of normal transferrin saturation [ 13 ]. In some infants and young children due to the dense opacity of the posterior lens capsule, it is often necessary to increase the laser energy or increase the number of firings, which may aggravate the degree of damage of corneal endothelial cells and iris tissue and increase the incidence of complications [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants in neonatal intensive care unit (NICU) have greater chances of developing sensorineural hearing loss (SNHL) because of the presence of multiple risk factors [ 12 ]. It has been reported that hereditary hyperferritinemia cataract syndrome (HHCS) should be considered in the differential diagnosis of childhood hyperferritinemia, especially in the presence of normal transferrin saturation [ 13 ]. In some infants and young children due to the dense opacity of the posterior lens capsule, it is often necessary to increase the laser energy or increase the number of firings, which may aggravate the degree of damage of corneal endothelial cells and iris tissue and increase the incidence of complications [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infants in neonatal intensive care unit (NICU) have greater chances of developing sensorineural hearing loss (SNHL) because of the presence of multiple risk factors [12]. It has been reported that hereditary hyperferritinemia cataract syndrome (HHCS) should be considered in the differential diagnosis of childhood hyperferritinemia, especially in the presence of normal transferrin saturation [13].…”
Section: Selection Of Different Types Of Posteriormentioning
confidence: 99%
“…However, our study does have several limitations. First, the sample size was relatively small, only the Chinese population was screened, and, compared with other small size group research, our description of family history and clinical symptoms is not comprehensive enough [50][51][52]. In addition, some research indicated that the mutation of WFS1 may also cause cataract, so we cannot exclude the possibility that the joint action of the CRYGD and WFS1 cause cataract and iris coloboma [37,53,54].…”
Section: Journal Of Ophthalmologymentioning
confidence: 99%
“…However, this number is probably underestimated because the disorder is often misdiagnosed as hereditary hemochromatosis due to hyperferritinemia, despite the absence of iron overload [ 3 ]. Actually, investigators often find out new cases with previously reported mutations, as in the case of Ferro and collaborators that described an Italian family [ 4 ]; for this reason, it is an important differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%